The Impact of Organizational Learning and Organizational Innovation on Organizational Performance: A Case of an Internet Service Provider in Myanmar - Thein Than Toe; Tantasanee, Somchai (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
This independent research has three main objectives: (1) to examine the factors impacting organizational performance, (2) to examine the impact of organizational learning on organizational innovation, (3) to help management to encourage and support organizational learning and oganizational innovation among employees. The researcher used quantitative questionnaires distributed to 141 people and interviewed 13 people. The researcher employed Simple Linear Regression and Multiple Linear Regression to analyze data from the questionnaire and contents analysis for the interviews. The quantitative findings indicated that organizational innovation has more impact on organizational performance than organizational learning. Moreover, the researcher found that organizational learning impacts organizational innovation while the qualitative findings implied that the organization should promote organizational learning and innovation to improve organizational performance. Based on the findings, it is recommended that (1) the organization should establish better and proper reward policies for new ideas and innovations proposed by employees and (2) it should provide more well-designed wellness programs to retain employees and create multiple recruiting strategies to attract talents and (3) the organization should encourage employees to improve their professional competencies actively.